TELECOMMUTING MODEL FOR SMALL AND MEDIUM ENTERPRISES (SMES) IN KENYA - Gakii, Consolata; Mwangi, Waweru; Okeyo, George (My University, 2016)
The aim of this study was to use adaptive structuration theory as a tool to come up with Telecommuting model that can be adopted by SMEs in Kenya. A survey was done to understand the extent of telecommuting and the available technological tools in the Kenyan SMEs. Data from this survey indicates that most of the workers have reliable and fast internet access away from the office and reliable information support team. These employees also reported improvement in quality and efficiency in terms of service delivery. This was attributed to the time available to concentrate on their tasks unlike in the office where there could be interruptions or meetings. A representative microfinance was chosen to understand the organizational structure and the information technology infrastructure available in a typical Kenyan SME. Results showed that the SME had both the IT infrastructure and personnel in place. Based on these findings, an AST derived model was developed and tested. Our study shows that adoption of the developed AST derived telecommuting model could lead to increased productivity, efficiency and quality of work. Findings from this study would assist stakeholders use the available infrastructure and personnel to allow formal telecommuting.
Keywords: Telecommuting; Cloud Computing; Adaptive Structuration Theory; Small and Medium Enterprises